Document analysis of academic studies on technology addiction - Ağgül, Esin; Yalçın, Paşa (Journal of Dependence, 2024)
Objective: This study aims to analyze academic research on technology addiction in Turkey through the qualitative research approach of document analysis. Method: To achieve this goal, a comprehensive search was conducted, accessing a total of 161 studies conducted in Turkey from 2000 to 2024. These studies were sourced from the YÖK thesis database and other relevant data outlets, encompassing 39 theses, 107 articles, 11 congress presentations, 1 workshop report, and 3 book chapters. However, only the studies conducted up to January 2024 were accessible during this search. The scope of the search included studies on technology addiction, digital gaming addiction, social media addiction, smartphone addiction, and internet addiction. Results: Research findings indicate that 2023 saw the highest volume of studies conducted, with Fırat University leading the tally. The majority of these studies focused on university students, suggesting a significant emphasis on research within higher education institutions. Among the topics explored, technology addiction, its predictors, and influencing factors emerged as prevalent themes. Quantitative research methods were predominantly employed, with a greater reliance on quantitative data analysis compared to qualitative approaches. Conclusion: Research on technology addiction predominantly employed quantitative methods, primarily focusing on secondary and higher education demographics. To delve deeper into preventing this addiction, qualitative research methods are often employed, necessitating the inclusion of teachers and parents as participant groups in the process.